2022
DOI: 10.1177/07356331221106918
|View full text |Cite
|
Sign up to set email alerts
|

Learner Engagement in a Business Simulation Game: Impact on Higher-Order Thinking Skills

Abstract: Higher-order thinking skills (HOTS) are reliable predictors of success in school and the workplace. A typical technique for encouraging higher-order thinking is to use instructional design interventions that engage learners in simple cognitive activities. Business simulation game (BSG) is one of the types of interactive learning environments that can increase HOTS. In addition, student engagement and attitude toward technology use are considered strong influences on HOTS. The study explored the effect of using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…This gives students a real-life experience of challenges associated with "meeting a common goal". Furthermore, adopting a collaborative learning approach within the highereducation system allows adult learners to acquire knowledge and competences in specific areas, such as team working skills, knowledge sharing, developing creativity, self-learning and developing essential skills for the workplace (Huang et al, 2023). Locke (1728) observed that experiential learning techniques assist students in storing information within their longterm memory, where it can easily be recalled.…”
Section: Experiential Learning In Enterprise Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…This gives students a real-life experience of challenges associated with "meeting a common goal". Furthermore, adopting a collaborative learning approach within the highereducation system allows adult learners to acquire knowledge and competences in specific areas, such as team working skills, knowledge sharing, developing creativity, self-learning and developing essential skills for the workplace (Huang et al, 2023). Locke (1728) observed that experiential learning techniques assist students in storing information within their longterm memory, where it can easily be recalled.…”
Section: Experiential Learning In Enterprise Educationmentioning
confidence: 99%
“…These skills are identified in the EntreComp Framework in Figure 1. They are considered reliable predictors of success in education and work settings (O'Brian and Costin, 2022; Huang et al. , 2023).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations